World histories from below disruption and dissent, 1750 to the present - Burton, Antoinette M. 1961-; Ballantyne, Tony 1972- (London Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
"This textbook is the first to consider world history from below, providing an alternative to the privilege of Western powers and elite political structures found in conventional global history narratives"--Provided by publisher.
" An emphasis on global structures and forces tends to privilege elites and their accomplishments, especially in the grand narratives of student textbooks. This book is an antidote to such studies and places 'ordinary' people and subordinated subjects at the heart of its analysis, arguing that disruption and dissent are overlooked agents of historical change. The contributors range from leaders in the field to rising stars, and cover themes including: religious conversions, political revolutions, labor struggles, and body politics. Each chapter takes a global view of the topic at hand, creating an accessible study of its subject from 1750 to the present day. World Histories From Below has the potential to refocus our entire approach to teaching world history "--Provided by publisher.
Includes bibliographical references and index.
Keywords: World history -- Textbooks; Social history -- Textbooks; Dissenters -- History -- Textbooks; Social conflict -- History -- Textbooks; Revolutions -- History -- Textbooks; Social change -- History -- Textbooks